International logistics : the management of international trade operations - David, Pierre A. (Cicero Books LLC, 2021)
"A full-color textbook covering all of the concepts of international logistics. This textbook is written from the perspective of shippers, those managers who are actively exporting or importing goods or are otherwise involved in international trade operations. All of the relevant issues are thoroughly explained, including documentation, terms of payment, terms of trade (2020 Incoterms© rules), exchange rate exposure hedges, international insurance, customs clearance, agency and distributorship sales contracts, contracts of carriage, packaging, transportation, warehousing, dangerous goods shipping, refrigerated goods shipping, as well as security issues"- Resumé vydavatel
Terminologický slovník
Keywords: logistika (management); mezinárodní obchod; mezinárodní obchodní operace; dopravní logistika; distribuce zboží; business logistics; international trade; international trade transactions; transportation logistics; distribution of goods; učebnice; textbooks